Redescription of Hyphessobrycon flammeus Myers, 1924 (Ostariophysi: Characidae), a threatened species from Brazil - Carvalho, Fernando R.; Jesus, Guilherme C. De; Langeani, Francisco (Sociedade Brasileira de Ictiologia, 2014)
One of the most gorgeous colored and endangered Hyphessobrycon species, H. flammeus Myers, is redescribed. Diagnostic characters of the species are two vertically elongated humeral spots, no caudal peduncle blotch, 5-8 maxillary teeth, caudal fin hyaline, and longitudinal dark stripe of the body absent. Sexual dimorphism is present, with males being more colored than females and having bony hooks in the anal and pelvic fins, which are dark in their terminal portions. Comments about its occurrence in the upper rio Tietê drainage (upper rio Paraná basin), its conservation status, and the phylogenetic position into Characidae context are also presented.

Uma das mais coloridas e ameaçadas espécies de Hyphessobrycon, H. flammeus, é redescrita. Caracteres diagnósticos para a espécie são duas máculas umerais verticalmente alongadas, mancha no pedúnculo caudal ausente, presença de 5-8 dentes no maxilar, nadadeira caudal hialina e faixa negra longitudinal no flanco ausente. A espécie apresenta dimorfismo sexual, com machos mais coloridos que as fêmeas e com ganchos ósseos nas nadadeiras anal e pélvica; além disso, as extremidades destas nadadeiras são enegrecidas. Comentários sobre a distribuição da espécie na drenagem do alto rio Tietê (bacia do alto rio Paraná), seu status de conservação e posição filogenética no contexto de Characidae são também apresentados.
Keywords: Characiformes; Engraçadinho; Flame tetra; Coastal streams; Endangered species